Finite element investigation of mechanism of stress on neck of two different stages after physiotherapy - Wong, Xin Yi. (2013)
In current study, a detailed two-dimensional of Finite Element Analysis (FEA) model of the cervical vertebra (neck) is generated based on 2 X-ray samples. Physical therapy was implemented on the cervical spine over a certain period of time to restore the optimal curvature of the neck. X-ray images of the neck were taken on day 1, 7, 16 and 21 respectively to check on the progress of the neck curvature. Simulated variations of different loads are applied to the 2 X-ray samples. Simulated hyperextension and hyper flexion of samples are generated too.